2018
DOI: 10.31234/osf.io/evm84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addiction, Identity, Morality

Abstract: Background: Recent literature on addiction and judgments about the characteristics of agents has focused on the implications of adopting a "brain disease" versus "moral weakness" model of addiction. Typically, such judgments have to do with what capacities an agent has (e.g., the ability to abstain from substance use). Much less work, however, has been conducted on the relationship between addiction and judgments about an agent's identity, including whether or to what extent an individual is seen as the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Subsequent studies found similar effects with other materials (Earp, Skorburg, Everett & Savulescu, 2019), across a wide variety of cultures and languages (Dranseika et al, unpublished data), and even in studies with children (Lefebvre & Krettenauer, 2020). For example, in a study that we will be discussing further below (Tobia, 2015; based on a case from Parfit, 1984), participants were given a vignette about a Russian nobleman.…”
Section: Good Vs Badmentioning
confidence: 54%
“…Subsequent studies found similar effects with other materials (Earp, Skorburg, Everett & Savulescu, 2019), across a wide variety of cultures and languages (Dranseika et al, unpublished data), and even in studies with children (Lefebvre & Krettenauer, 2020). For example, in a study that we will be discussing further below (Tobia, 2015; based on a case from Parfit, 1984), participants were given a vignette about a Russian nobleman.…”
Section: Good Vs Badmentioning
confidence: 54%